النوافذ الإسلامية في البنوك العمومية الجزائرية بين التحديات ومتطلبات النجاح (مجلة الواحات للبحوث والدراسات, 2020)
This Study Aims To Shed Light On The Reality And Requirements Of The Transformation Of Conventional Banks To Islamic Banking Through The Entrance Of Islamic Windows In Algeria. In Order To Achieve This Goal, We Relied On The Method Of The Survey By Distributing The Questionnaire To A Sample Of Three Public Banks (CNEP, BDL, BADR) Operating In Ghardaia, Concerned With Opening Islamic Windows.    The Results Of The Study Concluded That The Success Of Islamic Windows In Algerian Public Banks Is Subject To Providing A Set Of Necessary Requirements, Such As Issuing A Law On Islamic Banking, And That Islamic Banking Work Is Subject To The Supervision Of The Sharia Supervisory Board, And Developing Human Resources To Understand The Nature Of Islamic Banking And Its Legal Controls. Key Words- Transformation, Conventional Banks, Islamic Banking, Requirements, Islamic Windows.